Axial Bearing Capacity Analysis of Pile Foundation using Nakazawa Method - Laras Laila Lestari; Jaka Propika; Aisyah Dwi Puspasari (Jurnal IPTEK, 2020)
Pile foundation serves to distribute all the loads in the building to the ground. There are several calculation methods for bearing capacity of pile foundation, one of them is Nakazawa method. Nakazawa method adapted from calculation used in Japan where it is relevant for soft soils. The aim of this research is to obtain axial bearing capacity of pile foundation that can withstand axial forces using Nakazawa method. The parameter that used for the calculation is modified or average N-value (). The analysis result shows the  value is smaller than N existing, indicate that Nakazawa tend to use weaker value of N blows. It means the calculation is considered softer type of soils than the existing ones.The value of point bearing capacity, Rp, assimilate to the pattern of N-SPT. The result value of friction bearing, Rf, in respect of depth shows the linear trending. Rf along the pile depends on the friction interaction between soil and structure. This phenomena influenced by the soil type. The value of cohession along the pile augment, means the ability of soils to stick to the pile/structure is also high. It explains why the value of friction bearing is bigger in respect of depth.